2016
DOI: 10.1016/j.vaccine.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity and safety of a tetravalent measles-mumps-rubella-varicella vaccine when co-administered with conjugated meningococcal C vaccine to healthy children: A phase IIIb, randomized, multi-center study in Italy

Abstract: NCT01506193.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…These results concur well with other studies done elsewhere which showed the existence of a measles immunity gap between HIV positive and HIV negative children [34,41,42]. Low measles seroprotectivity among HIV sero positive children may be attributed to impaired vaccination response due to compromised immune system at the time of vaccination or accelerated waning of immunity due to impaired immunity [19,34,41,43].…”
Section: Discussionsupporting
confidence: 92%
“…These results concur well with other studies done elsewhere which showed the existence of a measles immunity gap between HIV positive and HIV negative children [34,41,42]. Low measles seroprotectivity among HIV sero positive children may be attributed to impaired vaccination response due to compromised immune system at the time of vaccination or accelerated waning of immunity due to impaired immunity [19,34,41,43].…”
Section: Discussionsupporting
confidence: 92%
“…3 Vaccination strategies adopted in childhood can require a high number of sessions 4 and the fulfillment of the entire vaccination schedule can be challenging for newborns, parents and health professionals. 5 This phenomenon is even more evident with the development and introduction of new vaccines. This makes the vaccination schedule more complex due to the further increase in the number of injections and immunization sessions.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Furthermore, co-administration reduces the number of visits and, therefore, decreases stress and discomfort for children and parents. 5 Combined vaccines are thoroughly tested before they are approved for marketing. The United States (US) Food and Drug Administration (FDA) and the European Medicines Agency (EMA) ensure that the new products are safe and effective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations